Sensorimotor Exercises and Enhanced Trunk Function: A Randomized Controlled Trial - Mueller, Steffen; Engel, Tilman; Mueller, Juliane; Stoll, Josefine; Baur, Heiner; Mayer, Frank (International Journal of Sports Medicine, 2018)
The aim of this study was to investigate the effect of a 6-week sensorimotor or resistance training on maximum trunk strength and response to sudden, high-intensity loading in athletes.Forty-three healthy, well-trained participants were randomized into sensorimotor (SMT; n=11), resistance training (RT; n=16) and control groups (CG; n=16). Treatment groups received either sensorimotor training (SMT) or resistance training (RT) for 6 weeks, 3 times a week. At baseline and after 6 weeks of intervention, participants' maximum isokinetic strength in trunk rotation and extension was tested (concentric/eccentric 30°/s). In addition, sudden, high-intensity trunk loading was assessed for eccentric extension and rotation, with additional perturbation. Peak torque [Nm] was calculated as the outcome.Interventions showed no significant difference for maximum strength in concentric and eccentric testing (p>0.05). For perturbation compensation, higher peak torque response following SMT (Extension: +24 Nm 95%CI±19 Nm; Rotation: +19 Nm 95%CI±13 Nm) and RT (Extension: +35 Nm 95%CI±16 Nm; Rotation: +5 Nm 95%CI±4 Nm) compared to CG (Extension: -4 Nm 95%CI±16 Nm; Rotation: -2 Nm 95%CI±4 Nm) was present (p<0.05).This study showed that isokinetic strength gains were small, but that significant improvements in high-intensity trunk loading response could be shown for both interventions. Therefore, depending on the individual's preference, therapists have two treatment options to enhance trunk function for back pain prevention.
Keywords: core; training intervention; prevention; perturbation; MiSpEx*